Evaluating Performance of Horizontal Axis Double Rotor Wind Turbines. Issue 1 (1st January 2019) - Bani-Hani, Ehab; Sedaghat, Ahmad; Saleh, Abdallah; Ghulom, Ahmad; Al-Rahmani, Hamad; Al-Zamel, Saqer; Lopez, Jessica
ABSTRACT: The current work investigates experimentally the performance of a double rotor horizontal axis wind turbine (DRHAWT). A second rotor is added to the traditional horizontal axis wind turbine (HAWT). The second rotor will restore the residual energy left in the wake of the first rotor; hence, increasing the output of the original wind turbine. For this purpose, two arrangements are examined; the first arrangement uses the second rotor directly after the first rotor, where both rotate in the same direction (concurrent), and the second arrangement uses the second rotor, where the rotors rotate in different directions (counter current). Small models are built and tested in the Australian College of Kuwait (ACK) wind tunnel setup. For comparison purposes, the base line one rotor HAWT is tested alone, then the two double rotors arrangements are tested, and the results are presented here. Power output and efficiency of these three designs are calculated and discussed. The experimental results conveyed an increase in the efficiency of the double rotor turbines compared with the single rotor turbine. It is indicated that the efficiency of the single rotor design is merely 15%, which raises to 18.1% for the double rotor counter rotating wind turbine. The efficiency is observed to be slightly more for the counter current double rotor turbine compared with the concurrent design.